Algebraic Expansion

If you expand the polynomial \left (a+b\right )^2, the resulting polynomial a^2+2ab+b^2 has three terms whose coefficients are 1, 2, and 1.  Find the sum of the coefficients of the terms in the expansion of \left (a+b\right )^{10} .
Source: mathcontest.olemiss.edu 5/5/2008

SOLUTION
We use the “area” model to represent the product of polynomials. For example, \left (a+b\right )\left (a+b\right ) is thought of as area=length\times width where length=\left (a+b\right ) and width=\left (a+b\right ).

The product \left (a+b\right )^2=\left (a+b\right )\left (a+b\right ) is calculated as follows:

 

a

b

                         

a

ab

                         

b

ab

                         

Thus, \left (a+b\right )^2=a^2+2ab+b^2.
Sum of the coefficients: 1+2+1=4.

The problem asks for the sum of the coefficients, not what the individual coefficients look like in the finished product so it is not necessary to combine the like terms before calculating the sum of the coefficients. Instead, we will leave all the like terms un-combined as follows:
\left (a+b\right )^2=a^2+ab+ab+b^2
. The sum of the coefficients is 1+1+1+1=4

Similarly, the product \left (a+b\right )^3=\left (a+b\right )\left (a^2+2ab+b^2\right ) is calculated as follows:

 

2ab

                       

a

2a²b

ab²

                       

b

a²b

2ab²

                       

Thus, \left (a+b\right )^3=a^3+3a^2b+3ab^2+b^3.
Sum of the coefficients: 1+3+3+1=8.

If we left the like terms un-combined, the same operation looks like this:

 

ab

ab

                     

a

a²b

a²b

ab²

                     

b

a²b

ab²

ab²

                     

All 8 coefficients are equal to 1. Their sum is 1+1+1+1+1+1+1+1=8.

Better yet, let’s leave out all the variables and just use the coefficients. The same operation looks like this:

 

1

1

1

1

                     

1

1

1

1

1

                     

1

1

1

1

1

                     

Let’s use this procedure and calculate the sum of the coefficients of \left (a+b\right )^4.

 

1

1

1

1

1

1

1

1

             

1

1

1

1

1

1

1

1

1

             

1

1

1

1

1

1

1

1

1

             

The sum of the coefficients equals 16.

For verification, let’s calculate the product \left (a+b\right )^4=\left (a+b\right )\left (a^3+3a^2b+3ab^2+b^3\right ) the old way and see if we get the same result:

 

3a²b

3ab²

                   

a

a⁴

3a³b

3a²b²

ab³

                   

b

a³b

3a²b²

3ab³

b⁴

                   

Thus, \left (a+b\right )^4=a^4+4a^3b+6a^2b^2+4ab^3+b^4.
Sum of the coefficients: 1+4+6+4+1=16.

General formula
Let S_i be the sum of the coefficients of \left (a+b\right )^i. Then,
\left (a+b\right )^2: S_2=1+1+1+1=4=2^2.
\left (a+b\right )^3: S_3=2\times S_2=2\times 2^2=2^3.
\left (a+b\right )^4:=2\times S_3=2\times 2^3=2^4.

In general, for \left (a+b\right )^n:
S_n=2\times S_{n-1}
=2\times 2^{n-1}
=2^n
.

Sum of coefficients of \mathbf{\left (a+b\right )^{10}}.
S_{10}=2^{10}=1024.

If you are familiar with the Pascal Triangle, you can derive the individual coefficients of \left (a+b\right )^{10} and calculate their sum as follows:
1+10+45+120+210+252+210+120+45+10+1=1024.

Answer: 1024.

Advertisements

About mvtrinh

Retired high school math teacher.
This entry was posted in Problem solving and tagged , , , . Bookmark the permalink.

One Response to Algebraic Expansion

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s